2019
DOI: 10.1002/ca.23458
|View full text |Cite
|
Sign up to set email alerts
|

Normal variations in position and relations of the median nerve in the carpal tunnel: A cross‐sectional observational study using clinical magnetic resonance imaging

Abstract: A standard relationship of the median nerve to neighboring tendons in the carpal tunnel has been described, but descriptions of normal variations are limited. The aim of this study is to describe the variation in position of the median nerve within the carpal tunnel and the variability in relation to adjacent tendons on clinical MR studies. A retrospective study was performed, analyzing 37 wrist MR examinations performed on a 3T MR machine. Primary endpoints involved measuring the four coordinates of the media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Other dynamic imaging studies of the carpal tunnel have been done using imaging systems including magnetic resonance imaging and ultrasound. [31][32][33][34][35][36][37] Wang et al 32 reported a significant reduction of dorsal translation of the MN in patients with CTS compared to non-CTS controls (n = 20 CTS cases; and n = 10 controls), whereas van Doesburg et al 38 observed no significant alternations in MN excursion between patients with CTS and healthy volunteers with fist motion. However, for other hand movements, including wrist flexion, studies have shown that the nerve displacement magnitude is less in patients with CTS compared to healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Other dynamic imaging studies of the carpal tunnel have been done using imaging systems including magnetic resonance imaging and ultrasound. [31][32][33][34][35][36][37] Wang et al 32 reported a significant reduction of dorsal translation of the MN in patients with CTS compared to non-CTS controls (n = 20 CTS cases; and n = 10 controls), whereas van Doesburg et al 38 observed no significant alternations in MN excursion between patients with CTS and healthy volunteers with fist motion. However, for other hand movements, including wrist flexion, studies have shown that the nerve displacement magnitude is less in patients with CTS compared to healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The median nerve usually enters the carpal tunnel radially, either superficial to the flexor digitorum superficialis tendons or between the flexor digitorum superficialis and flexor pollicis longus tendons, although nerve positioning may vary. 10 The roof of the carpal tunnel is the flexor retinaculum, also known as the transverse carpal ligament, that attaches to the scaphoid and triquetrum proximally and the trapezium and hamate distally. The floor of the carpal tunnel is made up of the proximal and distal carpal rows.…”
Section: Median Nerve Anatomymentioning
confidence: 99%
“…65 Both US and MRI can demonstrate an abnormal nerve course, focal nerve caliber change, and surrounding soft tissue edema (►Fig. 10). MRI can also demonstrate T2 hyperintense signal of the nerve, suggesting injury/neuritis.…”
Section: Wartenberg's Syndromementioning
confidence: 99%
“…Additionally, the tendon of the flexor pollicis longus (FPL) and the MN are passing through the CT [ 10 ]. Normally, the MN is located between the FR and the FDS, but its position within the CT may vary [ 11 ].…”
Section: Introductionmentioning
confidence: 99%